The Influence of Learning Strategies and Coordination Ability on Soccer Dribbling Skills - Hafiz, Auliya; Bakhtiar, Syahrial; Emral, Emral; Arsil, Arsil (Journal of Physical Education Health and Sport, 2023)
Based on the observations of researchers in the field, it can be seen that the football dribbling skills of Guguk Malintang Junior SSB students are still low. It is suspected that the learning strategies used by trainers are still less effective and also less attention is paid to students' coordination abilities. This study aims to determine the effect of cooperative learning strategies, inquiry learning strategies and coordination skills on soccer dribbling skills. This type of research is quasi-experimental. The population of this study were all 32 students of SSB Guguk Malintang Jumior who were registered at SSB. The sampling technique in this study used total sampling, so the sample in this study was 32 people. The instruments used in this study were the Körperkoordinationstest Für Kinder (KTK) test and the dribbling skill test. Data were analyzed using two way analysis of variance (ANOVA) and followed by a T-test. The results of the data analysis show that: (1) Overall, the football dribbling skills of Guguk Malintang Junior SSB students. those who were taught through the cooperative strategy had better results than the group of students who were taught through the inquiry strategy (Fcount = 2.515 Ftable = 2.048).(2) Overall there is a difference in the results of the treatment of football dribbling skills between groups of students who have high coordination abilities and students who have low coordination skills are accepted, because the calculation results show that Fcount = 28.18 Ftable = 4.20. (3) There is an interaction between the learning strategy and the ability to coordinate the soccer dribbling skills of Guguk Malintang Junior SSB students (Fcount =10.68 Ftable = 4.20).(4) In the group of students who have high coordination skills who are taught through a cooperative strategy the results are better than the group of students who are taught through an inquiry strategy(Qh=9.393 Q = 2.145).(5) In the group of students who have low coordination skills who are taught through cooperative strategies the results are better than the group of students who are taught through inquiry strategies(Qn = 0.530 Qt = 2.145).